Exosomes in esophageal cancer: a promising frontier for liquid biopsy in diagnosis and therapeutic monitoring - Zihan, Ren; Jingsi, Cao; Lingwen, Ding; Xin, Liu; Yan, Zhang (Frontiers in Pharmacology, 2024)
Esophageal cancer is a common and lethal digestive system malignancy, and both treatment efficacy and patient survival rates face significant challenges. In recent years, exosomes have emerged as crucial mediators of intercellular communication, demonstrating tremendous clinical potential, particularly in the diagnosis, treatment, and prognostic evaluation of esophageal cancer. These exosomes not only serve as biomarkers for early diagnosis and prognosis but also modulate tumor growth, metastasis, and drug resistance by delivering bioactive molecules. Importantly, exosomes can act as carriers for esophageal cancer-related therapeutic agents, optimizing gene therapy strategies to enhance efficacy while reducing toxicity and side effects. Despite facing challenges in clinical applications such as purification, enrichment, and standardization of analytical methods, exosomes maintain broad prospects for application in esophageal cancer treatment, with the potential to significantly improve patient outcomes and quality of life. This review focuses on the innovative role of exosomes in the early diagnosis of esophageal cancer, exploring their application value and safety in disease monitoring and assessment of treatment response. Furthermore, this study outlines the challenges and limitations of transitioning exosome research from basic studies to clinical applications, as well as potential solutions and future research directions to address these obstacles.